Resilience in engineered resilient systems. (October 2020) - Buchanan, Randy K; Goerger, Simon R; Rinaudo, Christina H; Parnell, Greg; Ross, Adam; Sitterle, Valerie
Dynamically transforming mission contexts in conjunction with ever-increasing budgetary constraints provides great impetus for the Department of Defense (DoD) to identify resilient systems early in the design process. The engineered resilient systems (ERS) community of interest (COI) research efforts focus on identifying and quantifying methods to perform systems engineering analysis in a model-based physics-driven environment. Research conducted has approached resiliency from various perspectives, including inherent resilience, mission and platform resilience, and value-driven resilient tradespace. This article examines resilience in an ERS context and presents multiple perspectives of resilience for consideration when developing modeling and simulation platforms to support analysis of systems under acquisition consideration.